Pengaruh Konsumsi Cookies Kerang Dara (Anadara Granosa) terhadap Perubahan Kadar Haemoglobin Wanita Usia Subur - Abdullah, Vera Iriani; Haumahu, C.H (Journal of Holistic Nursing Science, 2020)
In the world, around 1.62 billion people have low HB levels, around 30.2% occur in the group of women aged 15-49. In Indonesia, anemia cases rank 4th in the top 10 most disease groups. Prolonged iron deficiency can cause anemia, so it needs to be treated immediately so it doesn’t continue into pregnancy age which can cause complications until maternal and perinatal death. Papua has an abundance of marine wealth; one of those is Kerang Dara. Through this study, researchers wanted to explore the health benefits of nature. The aim is to see the effect of Consumption of Kerang Dara Cookies (Anadara Granosa) on Changes of Hemoglobin Levels of in Woman of Childbearing Age as an Effort to Prevent Anemia in District Aimas, Klaigit Village. Type of this research is quasi-experimental by pretest-posttest control group design method. The population of all the women of Childbearing who live in Klaigit Village, with a total sample of 14 people divided into 2 groups: control and intervention. Data collection techniques using random sampling. The time of data collection occurred for 2 weeks, starting from September 20th to October 4th. The results based on statistical tests using T-Test, then the value 884 is greater than the value of the table 0.05, then the conclusion is there is an Effect of Consumption Kerang Dara Cookies (Anadara Granosa) Towards the Increased of Woman of Childbearing Hemoglobin Levels in Klaigit Village in District Aimas in 2019.